Respiratory and Intramuscular Immunization With ChAdOx2-NPM1-NA Induces Distinct Immune Responses in H1N1pdm09 Pre-Exposed Pigs - Vatzia, Eleni; Allen, Elizabeth R.; Manjegowda, Tanuja; Morris, Susan; McNee, Adam; Martini, Veronica; Kaliath, Reshma; Ulaszewska, Marta; Boyd, Amy; Paudyal, Basudev; Carr, Veronica B.; Chrun, Tiphany; et al. (Frontiers in Immunology, 2021)
There is a critical need to develop superior influenza vaccines that provide broader protection. Influenza vaccines are traditionally tested in naïve animals, although humans are exposed to influenza in the first years of their lives, the impact of prior influenza exposure on vaccine-induced immune responses has not been well studied. Pigs are an important natural host for influenza, are a source of pandemic viruses, and are an excellent model for human influenza. Here we investigated the immunogenicity of the ChAdOx2 viral vectored vaccine, expressing influenza nucleoprotein, matrix protein 1 and neuraminidase in H1N1pdm09 pre-exposed pigs. We evaluated the importance of the route of administration by comparing intra-nasal, aerosol and intra-muscular immunizations. Aerosol delivery boosted the local lung T cell and antibody responses, while intra-muscular immunization boosted systemic immunity. These results will inform how best to deliver vaccines in order to harness optimal protective immunity.